The implementation of multicultural-based English language teaching in a language institution - Asrianti Asrianti; Iskandar Iskandar; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2022)
This research aims to explore how teachers implement multicultural-based English language teaching in a language institution and students' views of teachers' implementation of multicultural-based English language teaching. This research is qualitative with a case study design. In collecting the data, the researcher used direct observation by observing teaching and learning processes to find teachers implementing multicultural-based English language teaching and semi-structured interviews to explore the students' views. There are two main points of the findings of this study: 1) there are four dimensions of multicultural education exist in the teachers' implementation of multicultural-based English language teaching: content integration, knowledge construction process, prejudice reduction, and equity pedagogy; 2) Students have positive views toward the teachers' implementation of multicultural-based English language teaching. Thus, the researcher concluded that teachers and students have positive views towards implementing multicultural-based English language teaching, and teachers have been implementing multicultural-based English language teaching in their classes. Furthermore, similar studies in the future are better to discuss the implementation of multicultural-based English language teaching using other approaches or other theories to analyze different parts of it